Incidence of Low-Grade Testicular Injury in Orchidectomy Specimens Post-testicular Torsion - Aworanti, Olugbenga Michael; Hajduk, Piotr; Devaney, Deirdre; Quinn, Feargal; Awadalla, Sami (European Journal of Pediatric Surgery, 2018)
Introduction Following detorsion and orchidopexy for testicular torsion, predominantly animal studies have reported a risk of autoimmune and reperfusion injury to the contralateral testis. As a result, when testicular viability is compromised, orchidectomy is readily performed. This practice increases the likelihood of testes with potentially reversible injury being excised. We aim to determine the incidence of such occurrences and review the available evidence for and against early orchidectomy when testicular viability is doubtful.Materials and Methods Data for a 15-year period from two pediatric institutions on testicular torsion in children younger than 16 years were reviewed. Using a previously published grading system, the orchidectomy specimens in this cohort with early low-grade injury were analyzed. Low-grade injury suggests the possibility of restitutio ad integrum implying restoration of exocrine and endocrine function of the affected testes.Results Between both institutions, 222 scrotal explorations were performed for testicular torsion; 20 neonatal and 202 outside the neonatal period (age range [median]: 1–28 days [3 days] and 3 months–16 years [13 years], respectively). Of these scrotal explorations, 17 neonatal and 66 nonneonatal orchidectomies were required (85 vs. 33%, respectively; p < 0.0001). From these orchidectomy specimens, 5 (6%) were found to have low-grade injury. The ages of these five children ranged from 9 to 16 years (median 15, mean 13.6 years). Their symptom duration ranged from 8 to 37 hours (median 14, mean 18 hours) and two of these children had a preoperative ultrasound documenting no flow to the testis.Conclusion The finding of histopathological features that may represent salvageability of a torted testis occurs relatively rarely. Because of this possibility, appropriate intraoperative steps to check for reperfusion must be undertaken prior to orchidectomy. More evidence for the use of antioxidants and tunica albuginea decompression to improve testes salvage rates is required. The potential for exocrine and endocrine function if partial testicular atrophy occurs and the evidence for contralateral autoimmune testicular damage in pre- and postpubertal males require further investigation.
Keywords: testicular torsion; histopathology; sympathetic orchidopathia; reperfusion; injury; orchidectomy